Do neutrophil gelatinase-associated lipocalin and interleukin-18 predict renal dysfunction in patients with familial Mediterranean fever and amyloidosis?. (April 2014) - Deveci, Köksal; Korkmaz, Serdal; Senel, Soner; Deveci, Hulya; Sancakdar, Enver; Uslu, Ali U.; Deniz, Abdulkadir; Alkan, Filiz; Seker, Mehmet M.; Sencan, Mehmet
Abstract Background: The aim of this study was to evaluate whether neutrophil gelatinase-associated lipocalin (NGAL) and interleukin-18 (IL-18) predict renal disfunction in patients with familial Mediterranean fever (FMF). Methods: This prospective study consisted of 102 patients with FMF in attack-free period, and 40 matched healthy controls. Of the patients, nine were diagnosed as amyloidosis. The patients were divided into two groups according to eGFR as below 120 mL per minute and above 120 mL per minute. Also, patients were divided into three groups according to the degree of urinary albumin excretion as normoalbuminuric, microalbuminuric, and macroalbuminuric. The serum levels of IL-18 (sIL-18) and NGAL (sNGAL), and urinary levels of IL-18 (uIL-18) and NGAL (uNGAL) were measured by using ELISA kits. Results: The levels of sIL-18, sNGAL, uIL-18, and uNGAL were detected significantly higher in FMF patients, particularly in patients with amyloidosis, when compared to controls. sNGAL, uIL-18, and uNGAL were significantly higher in patients with eGFR < 120 mL per minute than in patients with eGFR ≥ 120 mL per minute. sNGAL, uIL-18, and uNGAL were correlated significantly with urinary albumin excretion, additionally, were inverse correlated with eGFR. The most remarkable findings of this study are of the higher values of sIL-18, sNGAL, uIL-18, and uNGAL in both normoalbuminuric FMF patients and patients with eGFR ≥ 120 mL per minute. Conclusions: The results of this study suggest that sIL-18, uIL-18, sNGAL, and uNGAL are reliable markers of early renal disfunction in FMF patients, and may let us take measures from the early stage of renal involvement.